2006
DOI: 10.5194/acp-6-4519-2006
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of LACIS as a CCN detector and its use in measuring activation and hygroscopic growth of atmospheric aerosol particles

Abstract: Abstract. A calibration for LACIS (Leipzig Aerosol CloudInteraction Simulator) for its use as a CCN (cloud condensation nuclei) detector has been developed. For this purpose, sodium chloride and ammonium sulfate particles of known sizes were generated and their grown sizes were detected at the LACIS outlet. From these signals, the effective critical super-saturation was derived as a function of the LACIS wall temperature. With this, LACIS is calibrated for its use as a CCN detector. The applicability of LACIS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…These are the water sub-and supersaturated modes for the temperature range above T 0 = 273.15 K, the water sub-, ice supersaturated, and the water super-and ice supersaturated modes below T 0 = 273.15 K. If the inlet dew point temperature is lower than the wall temperature, the inner tube walls are in equilibrium with the water vapor of the flow and the dew point temperature remains constant (water subsaturated mode). Applying this water sub-saturated mode for T > 273.15 K with inlet and wall temperature being identical, deliquescence and hygroscopic growth of aerosol particles can be investigated (Wex et al, 2006Voigtländer et al, 2008;Ziese et al, 2008;Niedermeier et al, 2008). With higher inlet dew point temperature compared to the wall temperature, supersaturation can be achieved as a result of the simultaneous heat and vapor diffusion, which occur at slightly different rates, because of the non-linearity of the water vapor pressure curve.…”
Section: Applications and Modes Of Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the water sub-and supersaturated modes for the temperature range above T 0 = 273.15 K, the water sub-, ice supersaturated, and the water super-and ice supersaturated modes below T 0 = 273.15 K. If the inlet dew point temperature is lower than the wall temperature, the inner tube walls are in equilibrium with the water vapor of the flow and the dew point temperature remains constant (water subsaturated mode). Applying this water sub-saturated mode for T > 273.15 K with inlet and wall temperature being identical, deliquescence and hygroscopic growth of aerosol particles can be investigated (Wex et al, 2006Voigtländer et al, 2008;Ziese et al, 2008;Niedermeier et al, 2008). With higher inlet dew point temperature compared to the wall temperature, supersaturation can be achieved as a result of the simultaneous heat and vapor diffusion, which occur at slightly different rates, because of the non-linearity of the water vapor pressure curve.…”
Section: Applications and Modes Of Operationmentioning
confidence: 99%
“…As a result a thin water film accumulates on the tube walls and the dew point temperature of the flow converges to the wall-temperature set point. With this method, critical supersaturations for cloud droplet activation and growth, including kinetic effects, can be studied (Wex et al, 2006Voigtländer et al, 2008;Niedermeier et al, 2008;Ziese et al, 2008).…”
Section: Applications and Modes Of Operationmentioning
confidence: 99%
“…The larger particles for which the present saturation in LACIS is adequate for activation grow dynamically. Earlier activation measurements (Wex et al, 2006) showed that the results for hygroscopically grown particles could be linked through a straight line. The results for dynamically grown particles, however, could be reproduced by a polynomial curve.…”
Section: Activationmentioning
confidence: 99%
“…The calibration of LACIS with respect to the supersaturation was done with ammonium sulfate particles (Wex et al, 2006). At each supersaturation the diameter of the investigated dry salt particles was varied until the critical diameter D crit was found.…”
Section: Activationmentioning
confidence: 99%
“…The supersaturated mode of operation was applied for the activation measurements (Wex et al, 2006). In contrast to the sub-saturated mode, the wall temperature (here varied between 5.51 • C and 5.82 • C) is below the dewpoint temperature (22.0 • C) of the aerosol and the sheath air.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%